ABSORB II: Comparable Clinical Outcomes Noted with ABSORB Scaffold and XIENCE Stents - Vinall, Maria (MD Conference Express, 2014)
Results from ABSORB II [Serruys PW et al. Lancet. 2014], the first study to compare an everolimus-eluting bioresorbable scaffold with an everolimus-eluting metallic stent, demonstrated similar 1-year clinical outcomes in patients with coronary artery disease.